Brak wiary a wykluczenie godności sakramentalnej małżeństwa - Leszczyński, Grzegorz (Ius Matrimoniale, 2019)
The Code of Canon Law of 1983 classifies the reasons for marriage invalidity in three different categories: diriment impediments, defects in matrimonial consent and lack or defect of canon form. Among different defects in matrimonial consent, in 1101 § 2, Code of Canon Law enumerates simulations. Simulation signifies that a person contracting marriage expresses marital agreement merely on the surface, excluding in reality through a positive act of the will the marriage itself, some essential elements or an essential property of marriage. The present article is an attempt of looking at the relation existing between the validity of marriage and the exclusion of the sacramental dignity, with the special consideration of the faith of the person.